Viewing Firearm Danger Through the Lens of Police Officers - Terrill, William (Homicide studies, 2023)
Despite danger being an integral part of officer decision-making during potentially lethal encounters (see Graham v. Connor), the study of officers’ perceptions of danger is scarce. Using a survey of over 800 police officers located in a large metropolitan police department, this study assesses officers’ perceptions of danger in different types of armed citizen situations involving various levels of citizen resistance. It also identifies various contextual factors and officer characteristics in relation to danger. The findings are used to inform future research, departmental policy, officer training, and the “objective reasonableness” standard put in place by the Supreme Court.